ANALISIS KETERKAITAN WORK-LIFE BALANCE TERHADAP MUTU PENDIDIKAN DENGAN KINERJA GURU SEBAGAI MEDIATOR - Putri, Devia Berliana; Sutarto, Joko; Isdaryanti, Barokah (STKIP Pesisir Selatan, 2025)
This study aims to analyze the relationship between Work-Life Balance (WLB), teacher performance, and educational quality by using teacher performance as a mediating variable that influences WLB on educational quality. This study uses a literature study method with a qualitative approach, where data is obtained from domestic and international scientific articles related to the discussed topic and then analyzed using thematic analysis techniques to find patterns and relationships between variables. The results of the analysis indicate that WLB has a positive influence on teacher performance because teachers who can maintain a balance between work and life tend to have higher motivation, focus, and creativity. Furthermore, teacher performance has been proven to play a significant role in improving educational quality because teachers with good performance can create effective and quality learning. In addition, it was found that the effect of WLB on educational quality is indirect, through improved teacher performance as a mediator. The novelty of this study lies in combining the three variables of Work-Life Balance, teacher performance, and educational quality in one conceptual analysis model that has not been widely studied before. These findings are expected to broaden understanding of the importance of teacher well-being in efforts to continuously improve educational quality.